Respuesta :

Answer:

Step-by-step Simplifying

6 + -3x = 4 + -1x + -3 + -2x

Reorder the terms:

6 + -3x = 4 + -3 + -1x + -2x

Combine like terms: 4 + -3 = 1

6 + -3x = 1 + -1x + -2x

Combine like terms: -1x + -2x = -3x

6 + -3x = 1 + -3x

Add '3x' to each side of the equation.

6 + -3x + 3x = 1 + -3x + 3x

Combine like terms: -3x + 3x = 0

6 + 0 = 1 + -3x + 3x

6 = 1 + -3x + 3x

Combine like terms: -3x + 3x = 0

6 = 1 + 0

6 = 1

Solving

6 = 1

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

Answer:

No Solutions

Step-by-step explanation:

ACCESS MORE